Continuidad y cambio social en la cultura material de la vida cotidiana - González Marcén, Paloma; Montón Subías, Sandra; Picazo Gurina, Marina (Complutum, 2007)
Historical research has implied mostly that the ways of human activity related to everyday life tend always and everywhere to be similar and without any change. In this path of history, domestic activities are presented as a constant factor and, therefore, distant from social, economic, ideological and political transformations that confer dynamism and creativity to changes in human societies. However, two archaeological case studies will be presented in which quotidianity and its material expression, as it can be observed in the organization of habitat and in the innovation and management of technological knowledge, show significant transformations creating new ways of daily living.